2021
DOI: 10.1021/acs.chemrestox.1c00224
|View full text |Cite
|
Sign up to set email alerts
|

Novel Solvent-Free Extraction Method for Analyzing Tobacco Heating Product Aerosols: An Analytical and In Vitro Toxicological Five-Way Product Comparison

Abstract: Harmful and potentially harmful constituents (HPHCs) in tobacco smoke are thought to be responsible for the increased health risks. Tobacco heating products (THPs) heat tobacco instead of burning it to achieve significantly fewer toxicants than conventional cigarettes. To assess the toxicity of THP aerosols, it is often desirable to extract the main constituents using a solvent method. In this study, we developed a high-speed centrifugal method for extracting the total particulate matter (TPM) from THPs to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Centrifugal Equipment. This high-speed centrifugal device mainly refers to modifications of the device described by Hongjuan Wang et al 31 The centrifuge tube cap is installed on the top of the centrifuge tube to seal and protect the centrifuge tube (50 mL), and the centrifuge tube cap is a spiral tube cap with a sealing ring. Multiple CFPs are placed in the filter placement cavity.…”
Section: Methodsmentioning
confidence: 99%
“…Centrifugal Equipment. This high-speed centrifugal device mainly refers to modifications of the device described by Hongjuan Wang et al 31 The centrifuge tube cap is installed on the top of the centrifuge tube to seal and protect the centrifuge tube (50 mL), and the centrifuge tube cap is a spiral tube cap with a sealing ring. Multiple CFPs are placed in the filter placement cavity.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors report similar findings. Wang et al reported that no mutagenic or genotoxic effects were observed for particulate-phase liquid extracts produced from five unnamed HTPs investigated using Ames and micronucleus assays [ 75 ]. Chapman et al exposed cells to HTP aerosol at the ALI and reported significantly reduced or no activity in the NRU assay, micronucleus assay, and Ames test for two prototype HTPs when compared to the 1R6F Kentucky reference cigarette [ 40 ].…”
Section: Reviewmentioning
confidence: 99%